THE QUALITY OF LTBI THESIS BACKGROUND - MARLINA TAMPUBOLON (LP2MTBM MAKARIOZ, 2021)
This study explores the quality of LTBI thesis particularly in background under the discussion of Teaching LearningStrategies based on the academic reasons, the supporting arguments, and genre written. The analysis reveals that the LTBIthesis serve the academic reasons but supported ny less rellevant argument. It is also found that the genre written aredominantly Analytical Text, which means that the writers want to explain the phenomena and the causal effect related to it.